An Analysis of the Obligations of COMESA Public Procurement Regulations: The Case of Zimbabwe’s Public Procurement Regulatory Framework - Panganayi, Freedom (South African Yearbook of International Law)
With the coming into force of the new Constitution in 2013, public procurement was given a constitutional status in Zimbabwe. The Constitution sets out vital principles that public procurement legislation must comply with. Moreover, it is a requirement of the Constitution that the governance of Zimbabwe must be pursued in accordance with Zimbabwe’s international law obligations. Zimbabwe is a founding member of the Common Market for Eastern and Southern Africa (COMESA). To accelerate interstate trade, COMESA promulgated Public Procurement Regulations (PPR) for regional competitive bidding across member states. The viability of the regional trade agreements is hinged on mutual cooperation. Pursuant to the foregoing, member states are required to domesticate international agreements into their municipal laws. In 2017, the Zimbabwean legislature passed the Public Procurement and Disposal of Public Assets Act 5 to give effect to the provisions of section 315(1) of the Constitution (Amendment No. 20), 2013. The public procurement reform agenda in Zimbabwe occurred close to a decade after the adoption of the public procurement regulations by COMESA in 2009. This article explores the obligations imposed on Zimbabwe pursuant to the public procurement regulations. This is done by identifying the public procurement principles enumerated in public procurement regulations, which are binding on member states. This article endeavours to answer the question: To what extent does the Zimbabwean legal framework conform to public procurement regulations? This article notes that the legal framework underlying public procurement in Zimbabwe, by and large, conforms to the bar set in the public procurement regulations. Nonetheless, it highlights Zimbabwe’s public procurement shortcomings. The article concludes by making possible legislative recommendations.